Four-dimensional ultrasonographic characterization of plaque surface motion in patients with symptomatic and asymptomatic carotid artery stenosis - Meairs, Stephen; Hennerici, Michael G. (Stroke, 1999)
BACKGROUND AND PURPOSE: In vitro studies of atherosclerotic plaque fracture mechanics suggest that analysis of local variations in surface deformability may provide information on relative vulnerability to plaque fissuring or rupture. We investigated plaque surface deformations in patients with symptomatic and asymptomatic carotid artery disease using 4-dimensional ultrasonography and techniques for measuring optical flow. - METHODS: Four-dimensional ultrasound examinations of carotid artery plaques were performed in 23 asymptomatic and 22 symptomatic patients with 50% to 90% stenosis of the internal carotid artery. Plaque surface motion during 1 cardiac cycle was computed with a hierarchical model-based motion estimator. Results were compared with plaque echogenicity and surface structure. - RESULTS: Of the 45 patients examined, plaque surface motion estimates were obtained for 18 asymptomatic and 13 symptomatic patients. There were no significant differences in echogenicity or surface structure of asymptomatic and symptomatic plaques (P>0.05). Results of motion estimation showed that asymptomatic plaques had surface motion vectors of equal orientation and magnitude to those of the internal carotid artery, whereas symptomatic plaques demonstrated evidence of inherent plaque movement. There was no significant difference in maximal plaque velocity between symptomatic and asymptomatic plaques (P<0.14). Maximal discrepant surface velocity (MDSV) in symptomatic plaques was 3.85+/-1.26 mm/s (mean+/-SD), which was significantly higher (P<0.001) than MDSV of asymptomatic plaques with 0.58+/-0.42 mm/s (mean+/-SD). - CONCLUSIONS: MDSV of carotid artery plaques is significantly different in asymptomatic and symptomatic disease. Further studies are warranted to determine whether plaque surface motion patterns can identify vulnerable plaques in patients with carotid artery stenosis.